2006
DOI: 10.1002/cphc.200500448
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Reorientation of Immunoglobulin G During Nonspecific Interaction with Surfaces

Abstract: To achieve a better understanding of the nonspecific adsorption process of proteins on solid surfaces, the mechanism of this interaction was investigated by a model system comprising the structurally flexible ("soft") protein goat anti-rabbit immunoglobulin G and a set of chemically defined surfaces. The thermodynamic properties of both protein and surfaces were derived from contact angle measurements by applying the Lifshitz-van der Waals acid-base approach, and the Gibbs free enthalpy of interaction was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244]. In relation to protein adsorption the applicability of FCS to reveal the aggregation of proteins in the solution or on the surface has been demonstrated [245,246].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 97%
See 1 more Smart Citation
“…The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244]. In relation to protein adsorption the applicability of FCS to reveal the aggregation of proteins in the solution or on the surface has been demonstrated [245,246].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 97%
“…That means, a freshly established protein layer is hardly resistant to elution whereas after a certain time period (scaling between a few minutes and several hours) proteins can even be found to be irreversibly attached to the surface. In this way it has been proven that the protein Immunoglobulin G (IgG) undergoes conformational changes on a variety of model surfaces [118]. By using a simple kinetic model the transition rates between the initial and the apparent equilibrium state could be quantified.…”
Section: Conformational Changesmentioning
confidence: 99%
“…Already during the minimization of structure B Vac , a proton transfer from the NH 3 + group of alanine to its COO À takes place, which means that the zwitterionic form is not stable without solvent molecules. This observation is consistent with a series of investigations on the stability of glycine in the gas phase (see for example Jensen and Gordon [41] and references given therein).…”
Section: Simulation B Vacmentioning
confidence: 99%
“…The mechanism was resolved recently and shows the difficulties of removal after adhesion due to conformational changes. [40] In this respect, providing surfaces as described here, which lead to A C H T U N G T R E N N U N G desorption prior to conformational changes, is of principal interest. [40] In summary, a novel biotin cellulose has been synthesized.…”
mentioning
confidence: 98%
“…[40] In this respect, providing surfaces as described here, which lead to A C H T U N G T R E N N U N G desorption prior to conformational changes, is of principal interest. [40] In summary, a novel biotin cellulose has been synthesized. Monolayers of this compound were obtained on glass after Langmuir-Blodgett transfer and were used to detect single molecules after specific binding onto a streptavidin coating.…”
mentioning
confidence: 98%